Comparing compliance behaviour of students and farmers: Implications for agricultural policy impact analysis - Denise Peth; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2018)
Increasing popularity of economic experiments for policy impact analysis has led to an ongoing debate about the suitability of students to substitute professionals as experimental subjects. To date, subject pool effects in agricultural and resource economics experiments have not been sufficiently studied. In order to identify differences and similarities between students and non-students, we carry out an experiment in the form of a multi-period business management game that is adapted to an agri-environmental context. We compare the compliance behaviour of German agricultural students and German farmers with regard to water protection rules and analyse their responses to two different green nudge interventions. The experimental results reveal that the direction of the response to the policy treatments is similar. Even unexpected behaviour could be reproduced by the student sample. Nevertheless, the magnitude of the treatment effects differed between the two samples. This implies that experimenters in the field of agricultural and resource economics could use the subject pool of students to analyse the direction of nudge policies. If predictions should be made about the magnitude effects, we suggest using a professional subject pool.
Keywords: 330; subject pool effect; green nudges; policy impact analysis; compliance behaviour